Unfolding the anticorrosive characteristics of TiO2–WO3 mixed oxide reinforced polyaniline composite coated mild steel in alkaline environment. Issue 6 (14th October 2018) - Krishnan, Athira; Joseph, Bency; Bhaskar, Krishna M.; Suma, M.S.; Shibli, S.M.A.
Abstract : Electrically conducting polymer incorporated coatings effectively replaced chromate coatings, once widely employed for corrosion deterrence but now strictly restricted due to the environmental hazards. Here polyaniline nanocomposite was prepared by in situ polymerization of aniline monomer in presence of TiO2 –WO3 powder, blended with PVC matrix and coated over mild steel specimens to evaluate its anti‐corrosion property in alkaline environment. Structural parameters of the composites and coatings were obtained from XRD and SEM‐EDS studies. Electrochemical parameters that govern the inhibitive efficiency of pigmented steel coupons were explored by Tafel polarization, electrochemical impedance spectroscopy, and open circuit potential measurements. The addition of (0.1 g) 1:1 TiO2 –WO3 to PANI (polyaniline) improve the protective efficiency of PANI from 65% to 97.5%. PANI/TiO2 –WO3 loaded specimen surface attained a state of passivity through uniform distribution of composite and characterized by the hydrophobic behavior that make it resistive to corrosive environment. Polarization studies identified the composite incorporated PANI as a mixed inhibitor. In order to extend the synthetic utility of prepared pigment, coated specimens are evaluated for their anticorrosive activity in acidic and mixed bacterial culture medium. The present work also included a detailed mechanism of passivation in view of the results of corrosion studies together with available literature studies. POLYM. COMPOS., 40:2400–2409, 2019. © 2018 Society of Plastics Engineers